Digital transformation of youth violence in Indonesia: new responsibilities and social negotiations in the digital age - Irwanto, Irwanto; Bahfiarti, Tuti; Unde, Andi Alimuddin (Frontiers in Communication, 2025)
Digital transformation has significantly changed how Indonesian society addresses youth violence. However, current frameworks fail to address the unique dynamics in collectivist digital environments. This perspective article examines the role of digital platforms as arenas for social negotiation and systemic change in Indonesia, introducing the Collective Resonance Communication Model (CRCM) to clarify information flows in collectivist cultures. By analyzing three notable cases of youth violence, we evaluate the influence of Indonesian cultural values on digital discourse and institutional accountability. Our findings indicate that collectivist digital spaces demonstrate greater cross-group interaction (15–25%) compared to individualistic environments, thus challenging previously accepted theories about digital echo chambers. The CRCM model outlines five essential components that illustrate how cultural values shape digital communication patterns and foster social change. By integrating cultural dimensions with digital dynamics, we propose a framework for understanding how collectivist societies utilize digital platforms to address youth violence while maintaining social harmony. These insights inform policy recommendations for culturally informed digital interventions.